Pengaruh Aktivitas Rasio Keuangan Terhadap Nilai Perusahaan Manufaktur Yang Terdaftar Di BEI - Michelle Angelita Tanudjaja, Rini Tri Hastuti (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study is to identify factors which effects firm value. Those factors including firm size, liquidity, profitability, and leverage. This study uses multiple linear regression and purposive sampling in testing factors that effect firm value. Samples in this study are manufacturing companies in Indonesia Stock Exchange from 2015 until 2017. The result also shows that Firm Size and Profitability (Return on Asset),while liquidity (Current Ratio) and leverage (Debt to Equity Ratio)do not have significant effect on firm value